PERUBAHAN BENTUK ERITROSIT DI GLOMERULONEFRITIS - Yosepha Dwiyana; Dalima AW Astrawinata (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
In glomerulonephritis there are intraglomerular inflammation, cell proliferation, and hematuria. Hematuria is characterized by more than 3 (three) erythrocytes per high-power field in the urine, which indicates the pathological processes in kidney or urinary tract. The combination of mechanical damage of erythrocyte membrane through the damaged glomerular basement membrane followed by the osmotic damage when it passes through the tubular system in the hypotonic osmotic solutions causes dysmorphic morphology. Erythrocytes trapped in the Tamm-Horsfall protein will form erythrocyte casts. Dysmorphic erythrocytes and or erythrocyte casts in the urine indicate glomerular hematuria. Various forms of dysmorphic erythrocytes in the urine can be found. Acanthocytes (G1-cells) are specific for glomerular hematury. The examination of these urinary sediments can be done natively or by using automated urinalysis analyzers.